Health insurance coverage, type of payment for health insurance, and reasons for not being insured under the National Health Insurance Scheme in Ghana - Martin Amogre Ayanore; Milena Pavlova; Nuworza Kugbey; Adam Fusheini; John Tetteh; Augustine Adoliba Ayanore; James Akazili; Philip Baba Adongo; Wim Groot (Health Economics Review, 2019)
Background: Ghana's National Health Insurance Scheme has improved access to care, although equity and sustainability issues remain. This study examined health insurance coverage, type of payment for health insurance and reasons for being uninsured under the National Health Insurance Scheme in Ghana. Methods: The 2014 Ghana Demographic Health Survey datasets with information for 9396 women and 3855 men were analyzed. The study employed cross-sectional national representative data. The frequency distribution of socio-demographics and health insurance coverage differentials among men and women is first presented. Further statistical analysis applies a two-stage probit Hackman selection model to determine socio-demographic factors associated with type of payment for insurance and reasons for not insured among men and women under the National Health insurance Scheme in Ghana. The selection equation in the Hackman selection model also shows the association between insurance status and socio-demographic factors. Results: About 66.0% of women and 52.6% of men were covered by health insurance. Wealth status determined insurance status, with poorest, poorer and middle-income groups being less likely to pay themselves for insurance. Women never in union and widowed women were less likely to be covered relative to married women although this group was more likely to pay NHIS premiums themselves. Wealth status (poorest, poorer and middle-income) was associated with non-affordability as a reason for being not insured. Geographic disparities were also found. Rural men and nulliparous women were also more likely to mention no need of insurance as a reason of being uninsured. Conclusion: Tailored policies to reduce delays in membership enrolment, improve positive perceptions and awareness of National Health Insurance Scheme in reducing catastrophic spending and addressing financial barriers for enrolment among some groups can be positive precursors to improve trust and enrolments and address broad equity concerns regarding the National Health Insurance Scheme.
Keywords: 330; Health insurance coverage; Type of payment; Insured and uninsured; National Health Insurance Scheme (NHIS); Ghana